Biodistribution of Sodium Pertechnetate and Light Microscopy of Organs Isolated from the Rats: Study of the Effects of a Ginkgo biloba Extract - Moreno, S.R.F.; Carvalho, J.J.; Nascimento, A.L.R.; Freitas, R.S.; Dire, G.F.; Lima, E.A.; Lima-Filho, G.L.; Rocha, E.K.; Bernardo-Filho, M. (Pakistan Journal of Nutrition, 2003)
Ginkgo biloba extract (EGb) is a phytoterapic used in the treatment of hypoxic conditions. This medicinal plant has several effects, specially, vasodilator, anti-inflammatory and anti-coagulant properties. It has antioxidant characteristics. Many substances have been reported to affect the biodistribution of different radiopharmaceuticals. We evaluated the influence of an EGb on: (i) the biodistribution of the technetium-99m (Tc-99m) and (ii) on the morphology of the organs from WISTAR rats. The animals were treated (6 days, intra gastric via) with EGb (40 and 400 mg/ml). After that, Tc-99m was injected and the animals were sacrificed. The organs were isolated and counted in a well counter. The percentages of radioactivity per organ (%ATI/organ) and radioactivity per gram (%ATI/gram) of each organ were calculated. Histological preparations were carried out with the pieces of organs (kidney, liver, duodena) withdrawn from the treated animals (400mg/ml EGb). The results showed that EGb altered (not significant, p>0.05) the biodistribution of the Tc-99m in the kidneys and liver. A significant (P